Stress and educational expectations: a study of future orientation - Sulma, Adrienne (University of Wisconsin--Stout. Research Services, 2014)
This research explores the extent to which the type of secondary education a student receives impacts their perceived stress level when it comes to thinking about college. Drawing from pace-of-life literature in educational and work-sphere studies, this research also explores whether the pace-of-life in educational institutions contributes to this perceived mental stress. This is a qualitative research project consisting of interviews with public school and alternative school (charter or home) students. Particular focus is given toward school norms on future-oriented pressures and whether the school provides leniency to lower performing students. Three theories were used for synthesis: structural strain theory, social learning theory, and fear appeal theory. This article argues that parents are most influential on a student’s perceived stress level in relation to future goals. The information collected from this study can inform school and parenting resources, and it indicates opportunities for future studies.
Keywords: stress; pace-of-life; adolescents; Motivation in education; Education; Stress management--Students; High school students--Psychology